High Methotrexate Triglutamate Level Is an Independent Predictor of Adverse Effects in Asian Indian Rheumatoid Arthritis Patients—A Preliminary Study. Issue 2 (April 2017) - Sandhu, Amit; Dhir, Varun; Bhatnagar, Archana; Dhawan, Veena; Kaur, Jasbinder; Sood, Ankita; Naidu, Shankar; Ahmad, Shabeer; Varma, Neelam; Sharma, Aman; Sharma, Shefali
Abstract : Background: It is unclear whether erythrocyte methotrexate polyglutamate levels (MTX-glun ) are associated with response or adverse effects to methotrexate in rheumatoid arthritis. This preliminary study evaluated their utility in Asian Indian patients over 24 weeks. Methods: Rheumatoid arthritis patients were started on oral methotrexate at a dose of 15 mg/wk, which was escalated to 25 mg by 12 weeks and continued till 24 weeks. Erythrocyte (RBC) MTX-glu1 to MTX-glu5 levels (nmol/L RBC) were determined at 4, 8, 16, and 24 weeks by using reverse-phase high-performance liquid chromatography. Area under the concentration curve (AUC) of MTX-glu1–5, MTX-glu3–5, and MTX-glu3 levels was compared between groups with regards to response and adverse effects. Results: This study included 117 patients with mean (SD) age of 42.7 (±11.9) years and disease duration of 2.0 (1.7) years. Mean (SD) RBC MTX-glu1–5 levels at 4, 8, 16, and 24 weeks were 93 (±29), 129 (±46), 143 (±49), and 159 (±65) nmol/L RBC; the highest individual polyglutamate was MTX-glu3 (40%). There was significant correlation between MTX-glu1–5 (r = 0.38, P < 0.001) and MTX-glu3 (r = 0.49, P < 0.001) with methotrexate dose. There was no significant difference of AUC MTX-glun between responders and nonresponders. However, AUC MTX-glu3 was significantly ( P = 0.03) higher in patients with adverse effects. On logistic regression, AUC of MTX-glu3 [odds ratio = 1.004 (95% confidence interval 1.002–1.007)] and methotrexate dose at 24 weeks were independent predictors of adverse effects. Conclusions: In this preliminary study, higher levels of RBC MTX-glu3 were found to be the independent predictors for adverse effects in rheumatoid arthritis patients.